Mekanisme Refinancing Syariah dalam Produk KPR Menggunakan Akad Musyarakah Mutanaqishah pada BTN KCPS Magelang - Syifa Al Murtadho; Miftahur Rahman; Achmad Abdul Fatah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the mechanism of Sharia Refinancing in mortgage (KPR) products using the Musyarakah Mutanaqisah contract at BTN KCPS Magelang. The main issue addressed is whether this practice aligns with the fatwa issued by the Indonesian Ulema Council (MUI) regarding Sharia Refinancing. This research uses a case study approach, specifically field research, which involves direct access to the field through interviews with relevant parties and the collection of data from BTN KCPS Magelang. This ensures the data is credible and accountable. The analysis is conducted deductively, drawing specific conclusions from general questions. The results of the study conclude that Sharia Refinancing can be carried out through Take Over or Top Up financing, where a customer has an asset financed by another bank but is no longer able to make the payments. Consequently, the customer applies for a loan from another bank to finance the same asset, a process referred to as Sharia Refinancing. In terms of the pillars and conditions, mechanisms, and provisions, the Sharia Refinancing process complies with MUI Fatwa No. 89/DSN-MUI/XII/2013. Customers are allowed to engage in this refinancing process, provided they adhere to the established pillars, conditions, mechanisms, and provisions.